Sadrian Philosophy and a Rational Interpretation of Revelation: With Emphasis on the Views of Ayatollah Jawadi Amoli - Seyyed Asif Ehsani (حکمت اسرا)
Mulla Sadra endeavors to provide a rational explanation of the nature of revelation and to open a rational perspective for understanding this phenomenon. The philosopher's inquiry into the essence of revelation is an attempt to render it comprehensible and to situate the origin of religion within the horizon of human reason. Revelation is perceived as an entirely rational process, and reason is declared to be its sole real and genuine foundation. In light of his intellectual framework, Mulla Sadra regards revelation as comprising various levels: intellectual, imaginal, linguistic, and sensory. He believes that the prophet is endowed with specific faculties, such as strong intuition, imagination, and the faculty of practical intellect, which enable him to receive revelation. Thus, the prophet, upon receiving intellectual truths, perceives their imaginal existence in the separate imaginal realm and, at the sensory level, hears the external manifestation of revelation in the form of sounds and letters. The prophet even observes the angel of revelation in the form of a human visage. According to Mulla Sadra's perspective, all these perceptions are produced by the prophet's own soul and are not the result of incarnation but rather of emanation. Ayatollah Jawadi Amoli, as an interpreter of Sadrian philosophy, seeks to address many of the questions and issues concerning revelation that have arisen in the modern era.